Social practices and energy use at home during the first Italian lockdown due to Covid-19. (March 2022) - Balest, J.; Stawinoga, A.E.
Abstract: During the beginning of the Covid-19 pandemic, cities became large residential consumers of energy. In general, energy demand has decreased, but the users who used the most energy during the pandemic were the people in their homes creating a change compared to the past. How have household habits changed affecting energy use during the lockdown? Has energy demand changed equally in all homes? What factors help explain the change in daily household habits and the change in energy use? Via distribution of a questionnaire completed by 3519 people living in Italy during the first lockdown #StayAtHome, the change in daily habits and consequent energy use were investigated. It collected data on socio-demographic and household characteristics and the material context in which people live. The results were interpreted according to the social practice approach that has been used in the past to analyse energy habits and use of households, for example, for cooking. The results can support the interpretation of energy demand studies in the pandemic period and address decisions and policymaking for sustainable energy transition. Highlights: The energy transition intersected with the Covid-19 pandemic. The increased time spent at home during the pandemic has impacted on energy use. Social practice of cooking rebalanced daily life during the lockdown. Socio-demographic characteristics impacted on energy use. Smart working and energy efficiency could be interrelated with energy demand.